Cultural Significance of Specific Costumes in Sinhalese Folk Theatre - Kankanamge, Sunethra (university of Sri jayewardenepura, 2017)
Attached

Each country has its own cultural significance which is reflected even in a play that is performed. If the play is a translation, the spectators go through the cultural, religious and political experience pertaining to that particular country as depicted in the context of the play. Theater costumes assume much significance here as they are specially used to surface the cultural significance in theatre. Also costumes provide the space for the actors to switch roles during a performance. This research focused on how to signify the cultural significance of the Sinhalese folk theatre, namely, Sokari, Kolam and Nadagam. Sokari is performed in the upcountry and has not been performed in the down south and the coastal area of the land. This is the oldest folk play the Sinhalese have. This is a theatrically rich play which has been performed after the harvesting period. Sokari is performed with specific costumes and this research attempted to analyze how these costumes represent the ancient period of the country and the cultural influence of neighboring India. Kolam is performed in the down south of the country and has not been performed in the other parts of the land. This performance always depicts the contemporary time of Sri Lanka. In this research I attempted to analyze how the costumes symbolize politicians, policemen and Mudliars of the country. Nadagam is performed in the coastal area of the country. This was influenced by Tamil Therukkuttu. With respect to Nadagam, I attempted to analyze how the costumes represent contemporary Sinhalese and Tamil culture. The source for primary data were the actual performances of particular plays. The secondary sources included the literature relevant to these areas.
Keywords: Folk theatre, cultural significance, Sokari, Kolam, Nadagam